SPORT: A REVIEW OF HEALTHY LIFESTYLE IN THE WORLD - Yudha Gusti Wibowo; Boy Indrayana (Jurusan Pendidikan Olah Raga dan Kepelatihan FKIP Universitas Jambi, 2019)
In recent decades, healthy lifestyle has occurred around the world. Everyone has been doing daily monotones routines such as working in industrial activities. Sport activities are new phenomena in twenty-first century to make everyone keep health. Sport could make our body is healthy, avoid heart disease caused by blockage of blood vessels. This article will describe how sport can be managed and governed to promote positive health outcomes. Sports are physical activity and give an impact like healthy, sports program must accessible, align with community needs, empowerment and encourage participant leadership. Sport should accessible for everyone in the world, children, young, adults, old man, sport including every age to get health and refreshing. The volume of regular physical activity has been frequently and consistently related to health benefits. Sport and exercise are contributors to the health of nations, the relation is curvilinear with the exact parameters of the curve varying for different health benefits